1998
DOI: 10.1111/1469-8986.3540405
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feedback signal and psychological characteristics on blood pressure self‐manipulation capability

Abstract: Blood pressure presentation mode and personality are likely to influence biofeedback outcome. Thirty-six normotensive subjects were randomly assigned to visual or auditory continuous systolic feedback. "Distracting speech" and "broad band noise" were also superimposed and the effect on the biofeedback response was investigated. Psychological influence was also investigated. Systolic pressure reduction of 4 +/- 4.3 mmHg (visual, p = .04) and 5 +/- 5.5 mmHg (visual + auditory, p = .03) were achieved compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…In addition, if the two feedback modes are not well combined, they may easily confuse the participants and adversely affect the feedback effect. Researchers who support using both types of feedback believe that the combination of the two allows participants to inadvertently ignore one feedback and rely on the other to remind them to continue to train (Lal et al, 1998;Vernon et al, 2004).…”
Section: Basis Of Nft Learning Theorymentioning
confidence: 99%
“…In addition, if the two feedback modes are not well combined, they may easily confuse the participants and adversely affect the feedback effect. Researchers who support using both types of feedback believe that the combination of the two allows participants to inadvertently ignore one feedback and rely on the other to remind them to continue to train (Lal et al, 1998;Vernon et al, 2004).…”
Section: Basis Of Nft Learning Theorymentioning
confidence: 99%
“…Traditional biofeedback research has shown that the mode of presenting sensory feedback can influence the response (Lal et al, 1998). Lal et al compared the use of visual, auditory or a combination of visual and auditory biofeedback to lower blood pressure in a group of thirty-six participants.…”
Section: Modality Of Feedbackmentioning
confidence: 99%
“…Raising and lowering the arm caused the BP feedback display to appropriately change, confirming the correct feedback prior to the commencement of the study. We wanted to assess the effect of background noise on the subjects' ability to control HR and BP as previous studies have suggested a detrimental effect (Lal et al 1998). The addition of background noise can be considered to more realistically simulate an actual environment in which conscious control might be undertaken by subjects either in the home, workplace or clinic where background noise is common.…”
Section: Measurementsmentioning
confidence: 99%
“…However, studies on normotensive subjects have been undertaken and are important in understanding differences in health and disease. Although it is generally agreed that normotensive subjects can significantly raise and lower HR using a variety of different techniques (Weems 1998, Lott and Gatchel 1978, James et al 1997, Pollard and Ashton 1982, there is mixed evidence as to whether BP can be consistently controlled in the same manner (Cejnar et al 1988, Lal et al 1998, Bowers and Murray 2004. The techniques employed in these studies included respiratory modulation (fast/deep breathing and breath holds) (Bowers and Murray 2004), as well as the use of both visual and auditory feedback (Cejnar et al 1988, Lal et al 1998.…”
Section: Introductionmentioning
confidence: 99%